INTERPROFESSIONAL COLLABORATION AMONG NURSES AND NURSING TECHNICIANS IN SAUDI ARABIA: ROLES, CHALLENGES, AND STRATEGIES FOR ENHANCING PATIENT CARE DELIVERY - Wasmiah Meshal Alanazi, Wesayf Fazza Aldaferi, Sara Hamed Jasser Alanazi, Sita Mulhan Hadi Alharbi, Amani Munawir Mekhldef Al-Dhafeeri, Badour Mukhalf Alanazi, Abdulaziz Ahmad Alshammari, Meshael Fadhel Alageel, Fadh Mazeed Alshammry, Maha Homoud O Alsham (Chelonian Research Foundation, 2022)
Interprofessional collaboration is essential for delivering high-quality, patient-centered care in healthcare settings. This study explored the roles, challenges, and strategies for enhancing collaboration among Nurses and Nursing Technicians in Saudi Arabia. A qualitative research design was employed, involving semi-structured interviews with a purposive sample of 30 Nurses and Nursing Technicians, including health informatics specialists, medical secretaries, dental assistants, nurses, and health assistants. Thematic analysis was used to analyze the data, and four main themes emerged: (1) roles and responsibilities, (2) interprofessional collaboration, (3) challenges and barriers, and (4) strategies for improvement. The findings highlight the importance of effective communication, mutual respect, and shared decision-making in collaborative practice, as well as the need for adequate resources, training, and organizational support to overcome challenges and enhance patient outcomes. The study contributes to the growing body of literature on interprofessional collaboration in healthcare and provides valuable insights for policy makers, healthcare organizations, and professionals in Saudi Arabia. Keywords: interprofessional collaboration, Nurses and Nursing Technicians, patient care delivery, Saudi Arabia